Strength and fragmentation behaviour of complex-shaped catalyst pellets: A numerical and experimental study. (23rd February 2020) - Farsi, Ado; Xiang, J.; Latham, J.P.; Carlsson, M.; Stitt, E.H.; Marigo, M.
Graphical abstract: Highlights: FDEM simulations are verified with disc crushing tests of catalyst support pellets. Undetected primary failure in laboratory tests are revealed using FDEM. FDEM allows detailed analysis of the fragmentation evolution of pellets. Compressive stress concentration in the pellet core generates a greater fraction of fines. FDEM reveals pellet shape susceptibility to reactor clogging and pressure drops. Abstract: The effects of catalyst support shapes on their final strength and fragmentation behaviour are investigated. Uniaxial compression tests by diametrical loading of solid and four-holed discs with high-speed video recordings are employed to investigate strengths and pellet crushing behaviours. The combined finite-discrete element method (FDEM) is employed to simulate the effects of geometrical features and loading orientation on the pre- and post-failure behaviour of catalysts. A comparison with experimental results is also presented and the remarkable agreement in failure evolution and mode is discussed. A methodology to derive representative fragment size distributions from defined pellet shapes and material properties is introduced, providing a further tool to understand the strength and fragmentation behaviour of catalyst supports. The results suggest that fixed-bed reactors made with solid cylindrical catalysts will be more likely to be affected by pressure drops caused by the choking effect of a significant portion of fines than if it was made with catalyst supports with four holes. Two designs of four-hole catalyst supports sintered with different porosities have also been studied, showing different fragment size distributions and fines production. Characterisation of fines production for different catalyst support designs will improve prediction of reactor clogging and pressure drops.